On the release of metronidazole from natural rubber latex membranes - Herculano, Rondinelli Donizetti [UNESP]; Alencar de Queiroz, Alvaro A.; Kinoshita, Angela; Oliveira, Osvaldo N.; Graeff, Carlos Frederico de Oliveira [UNESP] (Elsevier B.V., 2011)
The controlled release of drugs can be efficient if a suitable encapsulation procedure is developed, which requires biocompatible materials to hold and release the drug. In this study, a natural rubber latex (NRL) membrane is used to deliver metronidazole (MET), a powerful antiprotozoal agent. MET was found to be adsorbed on the NRL membrane, with little or no incorporation into the membrane bulk, according to energy dispersive X-ray spectroscopy. X-ray diffraction and FTIR spectroscopy data indicated that MET retained its structural and spectroscopic properties upon encapsulation in the NRL membrane, with no molecular-level interaction that could alter the antibacterial activity of MET. More importantly, the release time of MET in a NRL membrane in vitro was increased from the typical 6-8 h for oral tablets or injections to ca. 100 h. The kinetics of the drug release could be fitted with a double exponential function, with two characteristic times of 3.6 and 29.9 h. This is a demonstration that the induced angiogenesis known to be provided by NRL membranes can be combined with a controlled release of drugs, whose kinetics can be tailored by modifying experimental conditions of membrane fabrication for specific applications. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Metronidazole; Natural rubber latex; Drug delivery; Membranes; Biomaterials